SOCIAL DRAMATURGY ROLES PERFORMANCE IN BATMAN THE DARK KNIGHT RISES 2012 BY CHRISTOPHER NOLAN - Asyraf Sulaeman; Sape'i Sape'i (Saksama, 2022)
This study aims to analyze the social dramaturgy aspect in the film "The Dark Knight Rises" using the qualitative descriptive method. The study is guided by the sociological perspective of Erving Goffman, who proposed the concept of front and backstage behavior as a way to understand social interaction by its role. The objective of this study is to examine how the film represents the complex interplay between public and private behavior and how characters navigate different roles and expectations in their daily lives.The data was collected through a close reading of the film, focusing on the character interactions and the themes and symbols that are central to the narrative. The results show that "The Dark Knight Rises" portrays a complex interplay role behavior, with characters shifting between public and private roles depending on the situation.For example, the character of Batman is seen as a protector of the city in his role, while his private life is marked by his struggle with physical and emotional pain. Similarly, the character of Catwoman is depicted as a criminal in the role behavior reveals her to be a complex and multifaceted individual. Overall, this study demonstrates that the film "The Dark Knight Rises" provides a rich and nuanced representation of the social dramaturgy of daily life and highlights the ways in which characters navigate the interplay between public and private behavior. This study is significant because it sheds light on the role of the media in shaping our understanding of the complex interplay between public and private behavior and provides a useful lens through which to analyze the representation of social dramaturgy in popular culture.